A review of road traffic fatalities and countermeasures in sub-sahara Africa (2013)
Road traffic crashes are a major global problem. The problem is more acute in developing countries, especially in Sub-Saharan-Africa which has one of the worst road death rates in the world. The study therefore, evaluated road traffic fatalities and their countermeasures in selected countries in Sub-Sahara Africa. Data was collected from existing literature and secondary sources. Descriptive analysis such as tables of percentage was used for data analysis. Findings indicated that countries such as Angola and Sierra-Leone recorded over 100% and 200% increase in fatality rate respectively between 1999 and 2010, However; fatality rate dropped by between 17% and over 50% in countries such as Botswana, Namibia and Nigeria during the period of analysis. Estimates based on modelled data and reported cases of fatality rate showed a wide disparity in all selected countries in Sub-Sahara Africa. Also, human error comprising poor driving skill, alcohol intake and non-compliance with traffic rules and regulations accounted for more than 70% of the cause of road crashes in the region. An evaluation of 4Es (Engineering, Education, Enforcement, Emergency Response) adopted to ameliorate the rate of road carnage in these countries showed a modest achievement. Rumble strips reduced road fatalities by 55% in Ghana while Police increased enforcement also reduced crash death by 17%,in Uganda. The paper calls for improved method of road fatality data collection. appropriate road safety policies and regulations to stem road traffic fatalities particularly those associated with human error and increased political will to strengthen existing measures to reduce road carnage in Sub-Sahara Africa.